Establishment of ultrasound-responsive SonoBacteriaBot for targeted drug delivery and controlled release - Du, Meng; Wang, Ting; Feng, Renjie; Zeng, Penghui; Chen, Zhiyi (Frontiers in Bioengineering and Biotechnology, 2023)
Bacteria-driven biohybrid microbots have shown great potential in cancer treatment. However, how precisely controlling drug release in the tumor site is still an issue. To overcome the limitation of this system, we proposed the ultrasound-responsive SonoBacteriaBot (DOX-PFP-PLGA@EcM). Doxorubicin (DOX) and perfluoro-n-pentane (PFP) were encased in polylactic acid-glycolic acid (PLGA) to form ultrasound-responsive DOX-PFP-PLGA nanodroplets. Then, DOX-PFP-PLGA@EcM is created by DOX-PFP-PLGA amide-bonded to the surface of EcM. The DOX-PFP-PLGA@EcM composition was proved to have the characteristics of high tumor-targeting efficiency, controlled drug release capability, and ultrasound imaging. DOX could be released via acoustic droplet vaporization under ultrasound irradiation, which can be employed for both drug release and ultrasound imaging. DOX-PFP-PLGA@EcM can efficiently accumulate in tumors after being intravenously injected into tumor-bearing mice without causing harm to the mice's critical organs. In conclusion, the SonoBacteriaBot has significant benefits in real-time monitoring and controlled drug release, which has significant potential applications for therapeutic drug delivery in clinical.